Heavy metals removal from synthetic wastewater by a novel nano-size composite adsorbent - Onundi, Yusuf Bamidele; Al-Mamun, Abdullah; Al-Khatib, Ma'an Fahmi Rashid; Al-Saadi, M. A.; Muyibi, Suleyman Aremu (Center for Environmental and Energy Research and Studies, 2011)
The effects of varying operating conditions on metals removal from aqueous solution using a novel nano-size composite adsorbent are reported in this paper. Characterization of the composite adsorbent material showed successful production of carbon nanotubes on granular activated carbon using 1 % nickel as catalyst. In the laboratory adsorption experiment, initial mixed metals concentration of 2.0 mg/L Cu2+, 1.5 mg/L Pb2+ and 0.8 mg/L Ni2+ were synthesized based on metals concentration from samples collected from a semiconductor industry effluent. The effects of operation conditions on metals removal using composite adsorbent were investigated. Experimental conditions resulting in optimal metals adsorption were observed at pH 5, 1 g/L dosage and 60 min contact time. It was noted that the percentage of metals removal at the equilibrium condition varied for each metal, with lead recording 99 %, copper 61 % and nickel 20 % , giving metal affinity trend of Pb2+ > Cu2+ > Ni2+ on the adsorbent. Langmuir’s adsorption isotherm model gave a higher R2 value of 0.93, 0.89 and 0.986 for copper, nickel and lead, respectively, over that of Freundlich model during the adsorption process of the three metals in matrix solution.